Cherubino's leap : in search of the Enlightenment moment - Kramer, Richard, 1938- (The University of Chicago Press, 2016)
For the Enlightenment mind, from Moses Mendelssohn's focus on the moment of surprise at the heart of the work of art to Herder's imagining of the seismic moment at which language was discovered, it is the flash of recognition that nails the essence of the work, the blink of an eye in which one's world changes. In Cherubino's Leap, Richard Kramer unmasks such prismatic moments in a range of iconic instrumental works by Emanuel Bach, Haydn, and Mozart; in the musical engagement with the formidable odes of Friedrich Klopstock; and, on the grand stage of opera, at the intense moment of recognition in Gluck's Iphigenie en Tauride and the exquisitely introverted phrase that complicates Cherubino's daring escape in Mozart's Figaro. Finally, the tears of the disconsolate Konstanze in Mozart's Entf hrung inspire a reflection on the tragic aspect of the composer's operatic women. Other players from literature and the arts Diderot, Goethe, Lessing among them enrich the landscape of this journey through the Enlightenment imagination.